Piękno i dramat istnienia w poetyckich obrazach przyrody Marii Czerkawskiej - Hurnik, Elżbieta (Poznańskie Studia Polonistyczne. Seria Literacka, 2018)
The article is devoted to Maria Czerkawska’s poetry written during interwar period. Nature is the main subject of her poems. It is shown in a detailed and precise way. The good example is her book entitled Zielony cień (1928) and subsequent volumes. Zielony cień contains portraits of plants. Literary critics noticed several important features of these poems: versatility of observation, accuracy and concreteness of description. The same characteristics can also be observed in works of Skamander group of poets. Article focuses on the following topics: suffering observed in nature and continuous process of dying. Czerkawska’s poems tell us about transience, absurdity, horror and drama of existence. It is caused by close relation between the lyric subject and the nature. Czerkawska is trying to discover nature’s secrets. These tendencies are also present in poems of Bolesław Leśmian, Leopold Staff and Maria Pawlikowska-Jasnorzewska.